2017
DOI: 10.1038/ijo.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an obesity prevention program focused on motivating environments in childhood: a school-based prospective study

Abstract: A simple environmental intervention could effectively influence children. By adding to previously studied strategies, we can develop a more effective obesity prevention program for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
1
36
0
2
Order By: Relevance
“…Overall, twelve studies (33.3%) were conducted in the U.S., five studies (14.7%) were conducted in Australia and other countries in Oceania [ 24 , 25 , 26 , 27 , 28 ], and three studies (8.8%) in Brazil [ 5 , 29 , 30 ] and in Spain [ 31 , 32 , 33 ]. Other studies included countries within Europe [ 34 , 35 , 36 , 37 , 38 ] and Asia [ 39 , 40 , 41 ], Canada [ 42 ], Mexico [ 43 ], and Israel [ 44 ]. Programs were evaluated as controlled trials ( n = 31, 91.2%), randomized controlled trials ( n = 23, 67.6%), quasi-experimental ( n = 7, 20.5%), non-randomized ( n = 2, 5.8%), and as interrupted time series without a comparison group ( n = 3, 8.8%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, twelve studies (33.3%) were conducted in the U.S., five studies (14.7%) were conducted in Australia and other countries in Oceania [ 24 , 25 , 26 , 27 , 28 ], and three studies (8.8%) in Brazil [ 5 , 29 , 30 ] and in Spain [ 31 , 32 , 33 ]. Other studies included countries within Europe [ 34 , 35 , 36 , 37 , 38 ] and Asia [ 39 , 40 , 41 ], Canada [ 42 ], Mexico [ 43 ], and Israel [ 44 ]. Programs were evaluated as controlled trials ( n = 31, 91.2%), randomized controlled trials ( n = 23, 67.6%), quasi-experimental ( n = 7, 20.5%), non-randomized ( n = 2, 5.8%), and as interrupted time series without a comparison group ( n = 3, 8.8%).…”
Section: Resultsmentioning
confidence: 99%
“…For the energy-balance programs, 20 studies were found [ 24 , 25 , 30 , 32 , 34 , 37 , 38 , 39 , 40 , 41 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]; of these, five studies were conducted in the USA [ 45 , 46 , 47 , 49 , 50 ], six in Europe [ 32 , 34 , 35 , 37 , 38 ], four in Australia [ 24 , 25 , 26 , 27 ], three in Asia [ 39 , 40 , 44 ], and one in Brazil [ 30 ] and in Tonga [ 41 ]. When considering the study design, 13 studies were randomized controlled trials (RCT) [ 25 , 26 , 27 , 30 , 36 , 37 , 38 , 40 , 45 , 46 , 47 , 49 , 50 , 51 ]...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another school-based study showed that motivation was a major factor in influencing students to healthy lifestyles (25,26). This suggest that motivated students practiced healthy lifestyles that led to positive health outcomes among the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta-analysis by Wang et al [29] showed that school-based interventions contributed to improvement in any of the weight measurements in children in 22–67% of cases. The 2017 study, which included annual support interventions in the child’s environment, showed statistically significant improvements only in the BMI z -score, but changes in body structure (body fat and muscle mass percentages) were similar to those in the control group [30]. Nevertheless, the researchers considered the intervention to be effective in terms of the health impact.…”
Section: Discussionmentioning
confidence: 99%